Matthew Fontaine Maury: Pathfinder - Smith, Jason W (International Journal of Maritime History, 2016)
Historians have long recognized Matthew Fontaine Maury as an important if controversial figure in the histories of science and of maritime and naval affairs. These assessments, however, rest on scholarship that is by now more than a half-century old. It is therefore appropriate to look at Maury’s significance from fresh perspectives, incorporating recent historiographical trends in the history of science and cartography, environmental history, cultural history and military history. This article focuses on the ways in which Maury’s cartographic work reframed mariners’ understanding of the marine environment away from what he perceived to be a watery wilderness towards an ordered environment safe and favourable to American commerce. Maury was long known as ‘The Pathfinder of the Seas’, but I argue that his significance, in fact, lies in the ways he and his staff at the Naval Observatory organized the sea as a ‘common highway’, tracing paths, but also imposing narratives and constructing new meanings. Maury’s tool was the nautical chart and, particularly, his Wind and Current Charts series that by the 1850s reimagined the ways mariners, navigators and naval officers understood and harnessed the ocean environment. The article briefly considers these charts from three perspectives – method, process and representation – in order to see the ways in which Maury was pushing the boundaries of the cartographic medium to usher in revolutionary ways of envisioning the ocean environment. By quantifying winds, symbolizing whales and infusing the sea with ship tracks, among other things, Maury was imposing potent, if sometimes flawed, new ways of understanding and imagining the sea that were central to American maritime expansion in the antebellum era. In this and other ways, we can see Maury anew, a figure central to the growth of American commercial empire and to new ways of understanding and thinking about the sea.
Keywords: dept.his

Umayyad Caliphate - Judd, Steven C. (The Encyclopedia of Empire, 2016)
The Umayyad Caliphate (661–750) was the first Islamic dynasty. Muʿawiya ibn Abi Sufyan established himself as caliph in Damascus after his victory over ʿAli ibn Abi Talib in the civil war that followed the murder of ʿUthman ibn ʿAffan in Medina. Muʿawiya and his successors expanded the territory under Muslim rule dramatically. At their peak, the Umayyads ruled an empire stretching from Spain to the frontiers of China and India. The Umayyads made significant contributions to the development of the Islamic faith and to the spread of the Arabic language throughout the region. Dynastic crises, revenue shortfalls, and the limitations of an empire based on conquest ultimately led to their demise at the hands of the Abbasids in 750.
Keywords: 6th–10th centuries; Islam; Late Antiquity; Western Asia; dept.his; history; northern Africa; religious history

Soul sister journey: Essence magazine and travel columns during the “me” decad - Carter-David, S. (Women's Magazines in Print and New Media, 2016)
Keywords: dept.his

Were the umayyad-era qadarites Kāfirs? - Judd, S. (Islam. Hist. Civiliz., 2016)
Keywords: dept.his

Platonic words: Paolo sarpi and roberto bellarmino as translators in the venetian interdict crisis - Kern, D. (Philological Quarterly, 2016)
Keywords: dept.his; ⛔ No DOI found

To know the distance: Wayfinding and roadmaps of early modern England and France - Petto, C.M. (Cartographica, 2016)
In 1675, John Ogilby produced his road atlas with strip maps which not only arrived with fanfare, but spawned several more publications that aimed to be user-friendly. As with many maps and atlases from the London printing trade, the objectives were to serve consumers, acquire a piece of the market, and have an outlet for a new edition. Across the Channel, however, the road network of France, as with other public works, was not only state-directed but a tool of state power. Not until nearly one hundred years later did Claude-Sidoine Michel and Louis-Charles Desnos produce L'Indicateur Fidele, which provided strip maps for merchants, navigators, and travelers. This publication emerged out of the French national mapping project directed by the Cassini family. In the interim, while French map makers produced maps with an appeal to serving the state, they, like their London contemporaries, also hoped to maintain a thriving business and attract an audience, often through the traditional French social institution of patronage. The purpose of this comparative study of (post) road maps and atlases of England and France is to investigate the role of the government and the publishing trade in the production of these works. © 2016 University of Toronto Press.
Keywords: Consumers; England; France; London [England]; Map trade; Patronage; Post roads; Strip maps; United Kingdom; cartography; dept.his; mapping

Thou uncracked keel: The many voyages of the Whaleship Charles W. Morgan and the presence of the American Maritime past - Smith, J.W. (New England Quarterly-A Historical Review of New England Life and Letters, 2016)
The ship wherein Theseus and the youth of Athens returned from Crete had thirty oars, and was preserved by the Athenians down even to the time of Demetrius Phalereus, for they took away the old planks as they decayed, putting in new and stronger timber in their place, in so much that this ship became a standing example among the philosophers, for the logical question of things that grow; one side holding that the ship remained the same, and the other contending that it was not the same. © 2016 by The New England Quarterly. All rights reserved.
Keywords: dept.his

Spatial relations and the struggle for space: Friedrich Ratzel’s impact on German education from the Wilhelmine Empire to the Third Reich - Paddock, Troy (Journal of Educational Media, Memory, and Society, 2016)
This article examines the influence of Friedrich Ratzel’s idea of the struggle for space and its impact on cultural and national development depicted in German geography and history textbooks from the Wilhelmine era to the Third Reich. Ratzel’s concept of bio-geography conceived the state as a living organism that is the product of humanity’s interaction with the land and also facilitates humanity’s spread across the earth. German textbooks promoted a similar concept of the state in their portrayal of geography and history, the implications of which were appropriated by the National Socialists to support their geopolitical goals.
Keywords: Education; Friedrich ratzel; Geography instruction; History instruction; National identity; State; Textbooks; dept.his

Sexual violence and the military - Cyr, Heather D. (The Wiley Blackwell Encyclopedia of Gender and Sexuality Studies - Sexual Violence and the Military, 2016)
Keywords: dept.his; law; military; sexual assault; sexual harassment; sexual violence

Book Review: The guatemala reader: history, culture, politics - Vrana, Heather (Ethnohistory, 2016)
Keywords: book.review; dept.his

Book Review: Histories of health in southeast asia: perspectives on the long twentieth century. - Thompson, C. Michele (Pacific Affairs, 2016)
Keywords: book.review; dept.his; ⛔ No DOI found

Captured on the gold coast: “Illegal” enslavement, freedom and the pursuit of justice in dutch courts, 1746–1750 - de Kok, Gerhard; Feinberg, Harvey M. (Journal of Global Slavery, 2016)
In May of 1746, slaving captain Christiaan Hagerop illegally captured ten Gold Coast canoe paddlers, seven of whom were free Africans from Elmina and Fante. Hagerop subsequently sailed to Suriname, where he sold the paddlers into slavery. To appease the relatives of the captured men and to safeguard its reputation among local Africans, the Dutch West India Company (WIC) launched a search for the kidnapped paddlers. Six of the men were eventually located in Suriname in 1749, the seventh having died in slavery. While the Africans were transported back to the Gold Coast via Amsterdam, the WIC tried to have Hagerop extradited to its Gold Coast possessions to receive punishment for his crime. A legal battle over jurisdictional competence ensued in the Dutch Republic, the outcome of which was that the captain was made to stand trial in Amsterdam, but in the end he received very little punishment. © 2016 Copyright 2016 by Koninklijke Brill NV, Leiden, The Netherlands.
Keywords: Africa; Gold Coast; Slave Trade; Suriname; dept.his; wic

Book Review: RECEPTION OF WAR. A.S. bradford) war. antiquity and its legacy. pp. xvi + 176, maps. new york: oxford university press, 2015. cased. ISBN: 978-0-19-538090-3 (978-0-19-538091-0 pbk). - Nakamura, Byron (Classical Review, 2016)
Keywords: book.review; dept.his